Between a frightening Present and a disjoined Future. Recession and social vulnerability in the case of Greek Neets: Socio-demographics, facets of the Crisis’ Impact and the revival of the intergenerational transmission of poverty. - Papadakis, Nikos Eystathios; Drakaki, Maria; Kyridis, Argyris; Papargyris, Antonis (Advances in Social Sciences Research Journal, 2017)
The paper initially approaches definitional issues and proceeds in a brief overview of the state of play concerning NEETs (young people not in education, employment or training) in the EU, emphasizing the relation between youth unemployment and NEET rates. Then, based on some of the key findings of a recent quantitative research (carried out within the framework of the EEA Grants/ GR07-3757 Project), the paper maps Greek NEETs’ main characteristics today and presents findings related to the impact of the crisis in both Young people in total and NEETs’ life course, employability, public trust, civics and survival strategies. The research leading to several of the results presented in the present paper has received funding from the EEA/Norwegian Financial Mechanism 2009-2014, under the Project Contract n° EEA Grants/ GR07- 3757 (‘Neets2). The Project was carried out by the Centre for Educational Policy Development of the General Federation of Greek Workers (KANEP/GSEE) (Project Coordinator Partner), the Centre for Political Research & Documentation of the Department of Political Science at the University of Crete (KEPET/ UoC) and the Centre for Human Rights of the Department of Political Science at the University of Crete (KEADIK/UoC) (Project Partner 1). It was carried out from 15/12/2015 to 14/12/2016.